القوى المحركة للنظام السياسي الالماني والعملية السياسية - سلمان, احسان عبد الهادي (Journal of Legal and Political Studies, 2013)
The German political parties and interest groups are the main forces driving the German political system , which in turn contribute actively in establishing of the democratic system in Germany , an increase political awareness among voters German through the provision of programs and ideas and proposals for the formation of a political culture fit and achieve popular demands , as well as the existence of the Constitution and laws to regulate this process , in order to contribute to the political process and manage successfully. Germany has been able to achieve substantial progress in building democracy and the rule of law enjoyed by German citizen fundamental rights and welfare
Keywords: The Moving Forces; political System; Political Process; Political Parties; Interest Groups; Germany